2023
DOI: 10.3390/antiox12061282
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Heterocyclic Compounds Targeting Mitochondrial Calcium Homeostasis and Signaling in Alzheimer’s Disease and Parkinson’s Disease

Abstract: Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the two most common neurodegenerative diseases in the elderly. The key histopathological features of these diseases are the presence of abnormal protein aggregates and the progressive and irreversible loss of neurons in specific brain regions. The exact mechanisms underlying the etiopathogenesis of AD or PD remain unknown, but there is extensive evidence indicating that excessive generation of reactive oxygen species (ROS) and reactive nitrogen species … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 168 publications
0
3
0
Order By: Relevance
“…In congruence with this, several studies have highlighted that heterocyclic derivatives are e cacious compounds viable for the treatment of parkinson's and other neurodegenerative diseases (Vitorrio, Dank and Lelo, 2023; Kumar et al, 2020; Babalola et al, 2021). Heterocycles like caffeine, Nifedipine, Latrepirdine and Blarcamesine have been reported to target the homeostasis of mitochondrial calcium (Tapias et al, 2023). The potency and druggability of heterocyclic derivatives have engendered its approval for the treatment of certain diseases.…”
Section: Discussionmentioning
confidence: 98%
“…In congruence with this, several studies have highlighted that heterocyclic derivatives are e cacious compounds viable for the treatment of parkinson's and other neurodegenerative diseases (Vitorrio, Dank and Lelo, 2023; Kumar et al, 2020; Babalola et al, 2021). Heterocycles like caffeine, Nifedipine, Latrepirdine and Blarcamesine have been reported to target the homeostasis of mitochondrial calcium (Tapias et al, 2023). The potency and druggability of heterocyclic derivatives have engendered its approval for the treatment of certain diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Alzheimer’s disease’s pathogenesis has been linked to the dysregulation of intracellular calcium signaling. The hallmark lesions of this condition, such as the buildup of amyloid, the hyperphosphorylation of tau, and neuronal death, are brought on by increased intracellular calcium ( LaFerla, 2002 ; Tapias et al, 2023 ). All three studies of this review have reported increased measures of calcium signaling, i.e., calciretinin immunoreactivity and S-100β in the hippocampus and spinal ganglia of the MSG-treated animals ( Krawczyk et al, 2015 ; Rycerz et al, 2015 ; Krawczyk and Jaworska-Adamu, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no cure and since approaches targeting Aβ and tau have shown that these misfolded proteins are likely not causative, attention has shifted to other mechanisms, including those involving mitochondria [4]. Mitochondria are being explored because abnormalities in this organelle are found early in the course of the disease and can lead to many of the neuron-destroying consequences of AD [5][6][7]. The disruption of mitochondrial dynamics leads to mitochondrial fragmentation, generation of reactive oxygen species (ROS) and poor energy production [8].…”
Section: Introductionmentioning
confidence: 99%